Contribution of Self-Control and Social Skills on the Tendency Social Media Addiction - Ristra Sandra Ritonga; Mudjiran; Yanuar Kiram (International Conference on Education, Islamic Studies and Social Sciences Research)
Social media is now familiar to users of the internet in the World. The tendency of teenagers now who was gathered with friends or family will be busy with social media without any communication in the circle. The behavior that individuals were caused by the difficulty of individuals controlling themselves in playing social media and the lack of individuals in social skills. The study aims to determine the contribution of self-control and social skills to the tendency of social media addiction, especially in high school students. This research uses the quantitative method with correlational descriptive. The sample in this research is 290 students using purposive sampling. The research instrument uses self-control instruments, social skills and social media addiction tendency using polytomy data with a Likert scale model. The results showed that there was a significant contribution between self-control and social skills to the tendency of social media addiction to students. The level of significance of self-control contributions and social skills to the tendency of social media addiction is at a moderate level.